Electrical Energy Audit Analysis at Muara Batu Subdistrict Office, North Aceh - Richardo, R; Multazam, Teuku; Syukri, Mahdi; Alfisyahrin, A; Siregar, Ramdhan Halid (Geuthèë Institute, 2023)
The need for electricity is one of the important things in the advancement of technology and human civilization in all respects. So it is necessary to regulate the use of electrical energy properly. Thus, it is very important for us to regulate the use of electrical energy in terms of power usage by electrical loads. One way is by saving electrical energy. One way to save electrical energy is an energy audit. The audit report is the result of the audit plan which will be processed and analyzed further in energy management (electrical energy regulation). From the results of the energy audit, energy flows will be known which will provide an overview of energy use, so that a strategic plan can be prepared to control energy use better and of course be more energy and cost efficient. One aspect of an energy audit is an audit of lighting energy (lighting in an area), so it is very important for us to control the use of electrical energy loads, in this research the kit only audits electrical energy, from the lighting energy of the Muara Batu sub-district office, North Aceh, so that the use of electrical energy becomes economical. Efficient use of energy can be a solution that will be very profitable in efforts to increase comfort. When an office is able to carry out energy efficiency, it means that the office has benefited from savings in energy consumption costs in a certain period, then from these results there are funds available that can be converted for other needs such as adding facilities or replacing equipment, which will indirectly increase employee comfort or the office.